2010 Statutes, Administrative Regulations and Judicial Decisions of the Telecommunication Sector - Aranha, Marcio Iorio; Lima, João Alberto de Oliveira; Quelho, Renata Tonicelli de Mello (Law, State and Telecommunications Review, 2011)
Statutes, regulations, administrative and judicial decisions applied to the telecommunications sector in Brasil in 2010.